Circum-Galactic Medium in the Halo of Quasars - Ottolina, Riccardo; Falomo, Renato; Treves, Aldo; Uslenghi, Michela; Kotilainen, Jari K.; Scarpa, Riccardo; Farina, Emanuele Paolo (Frontiers in Astronomy and Space Sciences, 2017)
The properties of circum-galactic gas in the halo of quasar host galaxies are investigated analyzing Mg II 2800 and C IV 1540 absorption-line systems along the line of sight close to quasars. We use optical spectroscopy of closely aligned pairs of quasars (projected distance ≤ 200 kpc, but at very different redshift) obtained at the VLT and Gran Telescopio Canarias to investigate the distribution of the absorbing gas for a sample of quasars at z∼1. Absorption ̊ associated with the foreground quasars are revealed up to 200 kpc systems of EW ≥ 0.3 A from the centre of the host galaxy, showing that the structure of the absorbing gas is patchy with a covering fraction quickly decreasing beyond 100 kpc. We used optical and near-IR images obtained at VLT to investigate the relations between the properties of the circum-galactic medium of the host galaxies and of the large scale galaxy environments of the foreground quasars.